(untitled) (Journal of Universal Science Research, 2025)
The article considers the problem of building a decentralized architecture for controlling collaborative robots based on sensor networks, which is a relevant task for intelligent production systems of Industry 5.0. Mathematical models and expressions are proposed that describe information exchange between agents, conditions for safe interaction and coordinated movement.